Insights on How Museum Objects Mediate Recall of Nostalgic Life Episodes at a Shōwa Era Museum in Japan. (January 2016) - Anderson, David; Shimizu, Hiroyuki; Campbell, Chris
Abstract: Understanding visitors' nostalgic experiences in museums as they make connections between museum objects and their life histories is of considerable interest to the museum field. This study employed a qualitative multiple‐case narrative approach to understand the common characteristic themes about the nature of visitors' nostalgic recall, mediated though exhibits at a Shōwa era social history museum in Aichi Prefecture, Japan. Five sustaining characteristic themes about visitors' nostalgic recall are exemplified through five visitor cases in this study, including, a) Objects tied to collective identity and values perceived to be lost; b) Objects used or consumed as part of visitors' life‐scripts; c) Objects associated with individuals dear to the visitor; d) Objects associated with childhood; and e) Objects that invoke vicarious nostalgia. The outcomes of this study contribute to the broader understandings of the power of museum objects to incite strong nostalgic recollections and more broadly to our understanding of visitors' long‐term memories through their encounters with museum objects.